In Vitro and In Silico Biological Activities Investigation of Ethyl Acetate Extract of Rubus ulmifolius Schott Leaves Collected in Algeria - Amina Bramki; Djamila Benouchenne; Maria Michela Salvatore; Ouided Benslama; Anna Andolfi; Noureddine Rahim; Mohamed Moussaoui; Sourore Ramoul; Sirine Nessah; Ghozlane Barboucha; Chawki Bensouici; Alessio Cimmino; et al. (Plants)
This investigation aimed to assess the in vitro and in silico biological properties of the ethyl acetate (EtOAc) extract obtained from leaves of Rubus ulmifolius Schott collected in Algeria. The phytochemical screening data disclosed that flavonoids, tannins, coumarins, saponins, and anthocyanins were abundant. High levels of total phenolics, total flavonoids and flavonols (523.25 ± 3.53 µg GAE/mg, 20.41 ± 1.80, and 9.62 ± 0.51 µg QE/mg respectively) were detected. Furthermore, GC-MS analysis was performed to identify low molecular weight compounds. d-(-)-Fructofuranose, gallic acid, caffeic acid, and catechin were detected as main metabolites of the EtOAc extract. The outcomes revealed that the extract exerted a potent antioxidant apt, and ensured significant bacterial growth inhibitory capacity, where the inhibition zone diameters ranged from 20.0 ± 0.5 to 24.5 ± 0.3 mm. These outcomes were confirmed through molecular docking against key bacterial enzymes that revealed significant interactions and binding affinities. d-(-)-Fructofuranose was identified as the most polar and flexible compound. Gallic acid and caffeic acid demonstrated higher unsaturation. Caffeic acid was well absorbed in the blood–brain barrier (BBB) and human intestine. Catechin was well absorbed in CaCO3, and can act as an inhibitor of CYP1A2. These results highlight how crucial it is to keep looking into natural substances in the quest for more potent and targeted pathology therapies.